Assessing thyroid peroxidase antibodies in Emirati medical students: a cross-sectional pilot study - Pathan, Afrin; Yasin, Javed; Sharma, Charu; Alkaabi, Juma; Agha, Adnan (Frontiers in Endocrinology, 2025)
IntroductionAnti-thyroid peroxidase antibodies (TPO-Ab) are detectable in almost all patients with autoimmune thyroid disease or Hashimoto’s thyroiditis (HT) but may also be present in healthy individuals. HT affects women to a greater extent than men and can lead to overt hypothyroidism, which may increase the risk of miscarriage. There are no local data available on the prevalence of TPO-Ab among healthy women in the United Arab Emirates. The objective of this study was to determine the prevalence of TPO-Ab and assess thyroid function in healthy medical students.MethodsThis cross-sectional study used convenience sampling to recruit participants without any history of medical illness or prescribed medications from the College of Medicine at United Arab Emirates University, after obtaining informed consent. Routine demographic, anthropometric, and biochemical data—including TPO-Ab and thyroid-stimulating hormone (TSH) levels—were collected. The normal reference ranges for TPO-Ab and TSH (according to kit-specific recommendations) were 0–34 IU/mL and 0.27–4.20 mIU/L, respectively.ResultsA total of 90 healthy participants were enrolled (mean age: 19.83 ± 1.41 years), and all completed blood testing. All male participants (n = 27) had normal TPO-Ab levels, whereas eight female participants (12.7%; n = 63) had elevated TPO-Ab levels (mean: 40.03 ± 102.00 IU/mL). Three female participants (4.5%, n = 63) had elevated TSH levels without any clinical symptoms.ConclusionElevated TPO-Ab levels were observed in 12.7% (95% CI: 5.7%–23.5%) of young female participants. These preliminary findings suggest the need for larger prospective studies to evaluate the clinical significance of elevated TPO-Ab and possible related complications.